A Comparative Analysis of the Value System of the Discourse of Lorca’s The Moon Romance and Its Persian Translation by Shamloo - Fatemeh Bayatfar; Najmeh Shobeiri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Quality assessment of literary texts translation has always been irregular since some theorists believe that faithful translation to the original text is impossible. Therefore, through time, various theories for literary texts assessment have been created. In this paper with the comparative study of the value system of Lorca's "The moon" romance discourse and its Persian translation by Shamloo, has been emphasized the importance of discourse and context in the analysis and translation of literary texts, via investigating the factors such as assumption, previous background, utterances, the principle of cooperation, connection and coherence and theme. Besides, it has been shown that to what extent the translator could remain faithful to the source text by observing the discourse and context of the target language; as in this way Shamloo in the translation of “The moon” romance, has preserved all the linguistic coherence and also established rhetorical coherences except in one case. Therefore, by assuming that we know the necessity of paying attention to the discourse and context of the source-language and target-language in translation, Shampoo’s translation of “The moon” romance could be considered a faithful translation to the original text.